EFFECTIVENESS OF JIGSAW ON STUDENTS’ SPEAKING SKILL IN MAJALENGKA UNIVERSITY - Afief Fakhruddin (Jurnal Educatio, 2016)
EFFECTIVENESS OF JIGSAW ON STUDENTS’ SPEAKING SKILL IN MAJALENGKA UNIVERSITY Afief Fakhruddin.S.S.M.PdMajalengka UniversityMajalengka, Indonesiaafief_sa@yahoo.com AbstractThe research is entitled “The effectiveness of Jigsaw on students’ Speaking skill. The purposes of this research are (1) the levels of the speaking skill of the students   (2) to find out the effectiveness of jigsaw in students speaking skill, (3) the factors that influence the effectiveness of using Jigsaw in improving the speaking skill. This research belongs to experimental research and quasi experimental design. It describes about a study that cast about the effect of giving treatment of using Jigsaw in students speaking skill to an experimental group. The test result of posttest in experimental class showed that the students’ average is 72.06. It can be seen in proficiency level of speaking, majority of the students who got mark in the level of 3. The result of this study showed that the students in the experiment group got better development in the average scores than the control group in speaking test. The difference of the development of the average scores is statistically significant at the (0.5) alpha level of significance. It was found that there was significant difference for those who were taught using Jigsaw and those without it. The difference is shown by the development of the average scores. The group that used Jigsaw as medium in Jigsaw got better improvement in the average scores (15.39 ) than those without Jigsaw (0.684) Keywords – jigsaw, students speaking skill